Plant breeding increases spring wheat yield potential in Afghanistan - Sharma, Rajiv Kumar; Crossa, José; Ataei, Najibeh; Lodin, Raqib; Joshi, Arun Kumar; Vargas Hernández, Mateo; Braun, Hans-Joachim; Singh, Ravi P.; Bentley, Alison R. (Wiley, 2022)
Wheat (Triticum aestivum L.) is an essential food security crop in Afghanistan. To determine the contribution of wheat breeding to increasing productivity, we analyzed data obtained from 192 trials conducted over 11 locations from 2002–2003 to 2015–2016. Using this data, we estimated annual genetic gains for grain yield, days to heading and plant height over the 14-yr period. We used best linear unbiased estimates to measure genetic gains across CIMMYT Elite Spring Wheat Yield Trials per se and for the top 5 and top 10% performing genotypes relative to checks. Mean realized genetic gain for grain yield was 115 kg ha–1 yr−1, whereas the top 10 genotypes achieved annual yield gains of 123 kg ha–1. The continually replaced local check. s also contributed an annual genetic gain for yield of 107 kg ha–1. The associated adaptive traits days to heading and plant height varied in their response over time with the top 10 yielding genotypes having a 1.82 d annual reduction in heading date while plant height increased by 0.77 cm yr−1 for the same set of genotypes. Results show that continual breeding improvements confer yield gains, contributing to increasing Afghan wheat productivity. This has wider relevance for demonstrating the value of continued investment in public sector plant breeding supporting wheat production and food security in Central Asia.